HUBUNGAN KEKERASAN VERBAL DENGAN HARGA DIRI ANAK USIA 5-6 TAHUN DI LUNDAR KECAMATAN PANTI PROVINSI SUMATERA BARAT - Silvia Ningsih; Yeni Solfiah; Ria Novianti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article focuses on the study of the relationship between verbal violence and self-esteem for children aged 5-6 years at Lundar Panti in West Sumatra Province. The study was a quantitative research with the type of correlation research. The sample in the study involved 52 parents who have children aged 5-6 years at Lundar Panti in Pasaman of West Sumatra Province. The data collection technique was used through a questionnaire for the parents. Research analysis used the correlation test of Pearson product-moment assisted by IMB SPSS version 23. In conducting the study, the variable of verbal violence was categorized as high with the range of 66%-79%. Whilst the variable of self-esteem for children aged 5-6 years at Lundar Panti in West Sumatra Province was categorized as low with the range of 40%-55%. Based on the results, the Pearson product-moment value was 0.405 with a probability of 0.003. The correlation coefficient value was 0.405 in the range of 0.40-0.599, which meant that there was a relationship that was categorized as moderate between verbal violence and self-esteem directed to negative because the r-value was negative, which meant that the higher verbal violence was, the higher rvalue was, the lower children’s self-esteem was.